1995
DOI: 10.1007/bf02456616
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the last two exons of the mitochondrialnad7 gene results in lack of the NAD7 polypeptide in aNicotiana sylvestris CMS mutant

Abstract: In Nicotiana sylvestris, two cytoplasmic male sterile (CMS) mutants obtained by protoplast culture show abnormal developmental features of both vegetative and reproductive organs, and mitochondrial gene reorganization following homologous recombination between 65 bp repeated sequences. A mitochondrial region of 16.2 kb deleted from both CMS mutants was found to contain the last two exons of the nad7 gene coding for a subunit of the mitochondrial respiratory chain complex I, which is encoded in the nucleus in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…Two mitochondrial mutants with similar deletions have been described from Nicotiana sylvestris (Pla et al, 1995) and another mitochondrial DNA deletion mutant from maize (Zea mays; Karpova and Newton, 1999). A nuclear mutant almost lacking Complex I was observed in N. sylvestris (Brangeon et al, 2000), while three nuclear mutants affected in Complex I have been identified in Arabidopsis (Lee et al, 2002;Perales et al, 2005;Nakagawa and Sakurai, 2006).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Two mitochondrial mutants with similar deletions have been described from Nicotiana sylvestris (Pla et al, 1995) and another mitochondrial DNA deletion mutant from maize (Zea mays; Karpova and Newton, 1999). A nuclear mutant almost lacking Complex I was observed in N. sylvestris (Brangeon et al, 2000), while three nuclear mutants affected in Complex I have been identified in Arabidopsis (Lee et al, 2002;Perales et al, 2005;Nakagawa and Sakurai, 2006).…”
Section: Introductionmentioning
confidence: 69%
“…The best-characterized mutant to date is the CMSII mutant in N. sylvestris. This mutant carries a mitochondrial deletion in the nad7 gene encoding a 40-kD subunit of Complex I (Pla et al, 1995). The mutant plants develop slowly, exhibit conditional male sterility, and have no detectable Complex I, increased amounts and activity of AOX, and multiple perturbations to primary metabolism (Gutierres et al, 1997(Gutierres et al, , 1999Lelandais et al, 1998;Sabar et al, 2000;Dutilleul et al, 2003aDutilleul et al, , 2003bDutilleul et al, , 2005Pineau et al, 2005;Priault et al, 2006aPriault et al, , 2006bVidal et al, 2007).…”
Section: Plant Complex I Mutantsmentioning
confidence: 99%
“…Although no structurally intact complex is present in membranes of the nuoC-null mutant, a soluble 170 kD fragment corresponding to the NADH dehydrogenase module (NuoE/NDUFV2/24 kD, NuoF/NDUFV1/51 kD, NuoG/NDUFS1/75 kD) is still active (Erhardt et al, 2012). In tobacco (Nicotiana sylvestris), CMSI/II mutants are impaired in the expression of chloroplastic nad7 gene (Lelandais et al, 1998;Pla et al, 1995). As a consequence, rotenone-sensitive oxygen uptake is decreased and there is no complex I assembly (Gutierres et al, 1997;Pineau et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, deficiency in complex I function has been associated with several human diseases such as Leber's heredity optic neuropathy (Wallace et al, 1988), Leigh syndrome (Hoefs et al, 2008), and leukodystrophy (Holt et al, 1988), and complete absence of complex I is considered lethal. A number of plant mutants lacking respiratory chain components have been studied, including mutants in complex I (Marienfeld and Newton, 1994;Pla et al, 1995;Lee et al, 2002;Perales et al, 2005) and mutants removing specific nonphosphorylating bypasses such as AOX (Giraud et al, 2008). Mutants lacking complex II are embryo lethal in plants (Leon et al, 2007) and mutants lacking complex III or IV have not been reported, presumably as these are lethal in plants, as are mutants in the assembly of c-type cytochromes (Meyer et al, 2005).…”
mentioning
confidence: 99%
“…Mutants in genes encoding complex I subunits in Arabidopsis (Arabidopsis thaliana) include the 18-kD subunit (Lee et al, 2002) and the plant-specific CA2 subunit (Perales et al, 2005). Natural mitochondrial mutants lacking some of the mitochondrial nad genes as a result of genome rearrangements have been described in maize (Marienfeld and Newton, 1994) and Nicotiana sylvestris (Pla et al, 1995). Finally, several mutants have been identified in genes encoding splicing factors involved in the expression of nad4 in N. sylvestris (Brangeon et al, 2000) and Arabidopsis (Nakagawa and Sakurai, 2006) and of nad1 in Arabidopsis (de Longevialle et al, 2007).…”
mentioning
confidence: 99%